COMPARATIVE STUDY OF CUSTOMER SATISFACTION AND SERVICE QUALITY AT SHOPEE AND TOKOPEDIA - Zaatariyah, Razita; Muslihudin, Muslihudin; Nurhuda, Abid; Sinta, Dewi (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2023)
The existence of the digital marketing trend has attracted the public's attention, because of the many advantages of buying and selling online in terms of time, effectiveness, cost, and ease of controlling marketing. Furthermore, the societal phenomenon, namely the rise of online buying and selling transactions that are currently developing, has led to differences in consumer satisfaction and service quality in e-commerce used, especially at Shopee and Tokopedia. The purpose of this study was to determine the differences in customer satisfaction and service quality at Shopee and Tokopedia. This research is a quantitative study with a comparative study design and uses non-probability sampling in sampling and utilizes the Statistical Package for the Social Sciences (SPSS) version 26.00 to test the validity of the research. The results of this study prove that there is a difference between consumer satisfaction at Shopee and Tokopedia with an average value obtained by Shopee as much as 21.82 and an average value obtained by Tokopedia as much as 18.84. Then there is a difference in the quality of service received by Shopee and Tokopedia users with an average value obtained by Shopee as much as 17.89 and an average value obtained by Tokopedia as much as 16.12.